Fuzzy TOPSIS in selecting logistic handling operator: case study from Poland - Tubis, Agnieszka; Werbińska-Wojciechowska, Sylwia (Transport, 2023)
Reliable and effective selection of logistic handling operator is a particularly demanding process due to the short reaction time or high level of accompanying stress. Moreover, diversification of transported cargo makes use of classical indicators and methods of carrier selection highly unsatisfactory for decision-makers. To solve this problem, managers are seeking multi-criteria decision methods that improve the decision-making process related to the selection of the carrier and reduce the risk indicator related to the incorrect implementation of the transport order. Thus, in this paper, we present a Multi-Criteria Decision-Making (MCDM) approach for selecting logistic handling operators under partial or incomplete information (uncertainty) and taking into account the different type of transported cargo. The proposed approach comprises 2 main steps. In the 1st step, we identify the input parameters, mainly connected with criteria for carrier selection depending on the type of transported cargo. In the 2nd step, experts provide linguistic ratings to the potential alternatives against the selected criteria and the best alternative is chosen. At this stage, the fuzzy Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) approach is used. Later, the applicability of the developed method is presented based on the chosen case company. The comparison of classical and fuzzy approaches to decision-making process is also given.